ADVOKASI KEBIJAKAN DAN PENDAMPINGAN PENCEGAHAN KEKERASAN TERHADAP ANAK DI LINGKUNGAN SEKOLAH MENEGAH ATAS (SMA) KOTA BAUBAU - Abdullah, LOD; Pratiwi, ET; Abdullah, Rudi (INCIDENTAL : Journal Of Community Service and Empowerment, 2024)
The purpose of this community service is to carry out one of the tasks of the Tridharma of Higher Education and to provide advocacy to students and teachers about the dangers of criminal acts of violence against their students in the school environment, as well as how to report/complain to law enforcement. Overall, community service in the form of policy advocacy and assistance in preventing violence against children at the high school level has a significant impact in creating a safe, healthy, and supportive environment for children's development. This not only reduces the incidence of violence but also contributes to better educational quality.